2014
DOI: 10.1186/s12939-014-0111-5
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic factors associated with maternal health-seeking behaviours among women from poor households in rural Egypt

Abstract: IntroductionSocio-economic inequalities in basic maternal health interventions exist in Egypt, yet little is known about health-seeking of poor households. This paper assesses levels of maternal health-seeking behaviours in women living in poor households in rural Upper Egypt, and compares these to national averages. Secondly, we construct innovative measures of socio-economic resourcefulness among the rural poor in order to examine the association between the resulting variables and the four dimensions of mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
2
14
0
2
Order By: Relevance
“…In general, women with low socioeconomic status commonly show poor care-seeking behavior and health outcomes [40,41]. However, we found that they were more likely to have attended ANC at least four times if they had enrolled in the health insurance scheme.…”
Section: Discussionmentioning
confidence: 73%
“…In general, women with low socioeconomic status commonly show poor care-seeking behavior and health outcomes [40,41]. However, we found that they were more likely to have attended ANC at least four times if they had enrolled in the health insurance scheme.…”
Section: Discussionmentioning
confidence: 73%
“…A similar study in Egypt reported only 58.5% of mothers accessing ANC services before delivery [6]. Zimbabwe is one of the countries in Africa that are doing well in terms of promotion of access of MNCH services during pregnancy.…”
Section: Mnch Practices and Maternal Health Outcomesmentioning
confidence: 98%
“…There was higher likelihood of early ANC booking amongst mothers who could make independent decisions on maternal and child health and those families who jointly made decisions on MNCH yet there was less likelihood on the same in highly patriarchal families where the husband was the pivot for all decision made on health and other facets of life. A study by Banke et al revealed that use of ANC services predicted use of skilled birth attendance and use of both predicted use of PNC services [6]. A study in Nepal revealed that men with higher household income were more likely (AOR: 5.91, 95% CI 4.02, 8.70) to have ANC with their wives than man with no education or with primary level education [11].…”
Section: Mnch Practices and Maternal Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketersediaan fasilitas sanitasi, air bersih yang aman, standar bangunan tempat tinggal serta konsumsi zat gizi dapat mempengaruhi kesehatan ibu hamil. Dalam penelitian lain Benova et al, (2014) menyatakan bahwa kondisi ekonomi, sosial budaya dan kualitas tempat tinggal berhubungan positif dengan kualitas ANC. Sedangkan menurut Azhar, Dharmayanti and Ma'ruf (2016) mengamati bahwa status sosial ikut berperan dalam pelayanan kesehatan maternal yang berkesinambungan.…”
Section: Abstrakunclassified